ANALISIS KINERJA VOLUMETRIK DAN RUTTING CAMPURAN ASPAL PG76 DENGAN FLY ASH SEBAGAI PENGISI - Hermon Frederik Tambunan; Bernaditha Catur Marina; Boy Sipayung (Jurnal Infrastruktur, 2026)
Hot Mix Asphalt (HMA) used in the Asphalt Concrete–Wearing Course (AC-WC) layer is susceptible to permanent deformation (rutting), particularly due to high service temperatures, aggregate characteristics, and binder properties. This study aims to evaluate the effect of binder type, namely Penetration 60/70 asphalt and Performance Grade (PG) 76 asphalt, combined with fly ash (FA) as a filler, on the volumetric and rutting performance of AC-WC mixtures. The evaluation was conducted through Marshall volumetric parameters (VIM, VMA, and VFB), Marshall stability, Index of Retained Strength (IRS), and permanent deformation parameters under various testing temperatures. The results indicate that the mixture with PG76 binder exhibits a lower Optimum Asphalt Content (OAC) of 6.5% compared to 6.6% for the Pen 60/70 mixture, indicating higher binder efficiency. Volumetric analysis shows that the addition of fly ash has a strong correlation with changes in VIM, VMA, and VFB, with correlation coefficients greater than 0.7, highlighting the significant role of FA in improving the internal structure of the asphalt mixture. In terms of mechanical performance, the PG76 + FA mixture achieves a Marshall stability of 1686.04 kg, which is higher than that of the Pen 60/70 + FA mixture at 1407.58 kg. Moisture damage resistance is significantly enhanced by the addition of fly ash, as indicated by IRS values exceeding 90% for both binder types. Rutting performance results show that the PG76 FA mixture exhibits higher dynamic stability and lower permanent deformation, particularly at elevated temperatures. Overall, the combination of fly ash as filler and PG76 binder proves to be more effective in enhancing the volumetric characteristics and rutting resistance of AC-WC mixtures, making it suitable for overlay applications under heavy traffic and tropical climate conditions.